Efeito da mudança do calendário competitivo durante a pandemia de COVID-19 nos Jogos da Liga Nacional de Futsal (LNF) - Almeida, Samuel Rodrigo Azevedo de (Brasil, 2023)
At the beginning of 2020, the COVID-19 pandemic brought to all humanity a new reality, conditioning all the countries of the world to a series of restrictive measures in various areas, in order to contain its progress. In sports, it was no different and events were postponed, like the 2020 Olympics. The present study aimed to analyze the 2019 and 2020 seasons of the National Futsal League (LNF), before and during this pandemic period. With the beginning of the pandemic, many sports had to adapt their calendars due to the stoppage of events, which directly influenced the athletes and even more when there was a return to activities for the return of the training routine. For the development of this research, an analysis of the 19 teams participating in the (LNF) in 2019 and 21 teams in the 2020 season was carried out. The following results were obtained: there was no significant difference in any comparison variable of the years 2019 and 2020, there was no difference in the interval time of the days, with respect to the field assignment the most noticeable results were the fact that the visitors receive more cards and finish less, and the teams better positioned in the final table score more goals, when compared to the last-placed and intermediate teams. Thus, it was possible to conclude that even with the significant change in the number of games in the two seasons, there was no relevance regarding the variables presented, which may lead to the fact that in the 2019 season all teams face each other in two games and in 2020, they do not.